Short Bowel Syndrome and Kidney Transplantation: Challenges, Outcomes, and the Use of Teduglutide - Elizabeth Abou Diwan; Ankit B. Patel; Alex G. Cuenca; Nahel Elias; Hannah M. Gilligan; Eliot Heher; David E. Leaf; David Wojciechowski; Kassem Safa (Case Reports in Transplantation)
Among patients with short bowel syndrome who commonly have kidney disease, kidney transplantation remains challenging. We describe the clinicopathologic course of a 59-year old man with short bowel syndrome secondary to Crohn’s disease who underwent a deceased donor kidney transplant that was complicated by recurrent acute kidney allograft injury due to volume depletion from diarrhea, ultimately requiring the placement of permanent intravenous access for daily volume expansion at home resulting in the recovery of allograft function. Teduglutide treatment at 1.8 years post-transplant led to a dramatic decrease in diarrhea. A literature review of similar cases yielded 18 patients who underwent 19 kidney transplants. Despite high rates of complications, at the time of last follow-up (median 2.1 years [0.04-7]), 94% of the patients were still alive and 89% had functioning allografts, with a median eGFR of 37.5 [14-122] ml/min/1.73m2. In conclusion, despite high rates of complications, kidney transplantation in patients with short bowel syndrome is associated with acceptable short- and midterm outcomes. Further, we report for the first time the effects of the glucagon-like peptide-2 analogue teduglutide for short bowel syndrome in a kidney transplant recipient.